2015
DOI: 10.1016/j.mhpa.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on sleep among young women with Generalized Anxiety Disorder

Abstract: Statement of the Problem Generalized Anxiety Disorder (GAD) and disturbed sleep are prevalent, debilitating, and frequently comorbid problems for which successful treatment remains limited. Exercise can promote sleep but whether it does among GAD patients is unknown. Methods Thirty sedentary women (18–37y) with a primary DSM-IV diagnosis of GAD were randomized to six weeks of resistance (RET) or aerobic exercise training (AET), or waitlist (WL). RET and AET involved twice-weekly sessions of either lower-body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Studies with multiple exercise interventions groups (e.g. aerobic training group vs resistance training group vs control), the exercise or 'active' intervention groups (Herring et al, 2015;Strid et al, 2016) were pooled for analysis as per Cochrane Handbook (table 7.7a) recommendations (Higgins and Green, 2005). For studies reporting separate sleep data for weekends/ weekdays, weekday data were analysed.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with multiple exercise interventions groups (e.g. aerobic training group vs resistance training group vs control), the exercise or 'active' intervention groups (Herring et al, 2015;Strid et al, 2016) were pooled for analysis as per Cochrane Handbook (table 7.7a) recommendations (Higgins and Green, 2005). For studies reporting separate sleep data for weekends/ weekdays, weekday data were analysed.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Of the included studies, three studies were conducted in the United States (Field et al, 2013;Lavretsky et al, 2011;Singh et al, 1997), and one in Australia (Rosenbaum et al, 2015), Sweden (Strid et al, 2016), Ireland (Herring et al, 2015), Norway (Flemmen et al, 2014) and Switzerland (Colledge et al, 2017). and Insomnia Severity Index (ISI) (N = 2) were the two most frequently used tools with the Karolinska Sleep Questionnaire (KSQ) and Snyder-Halpern R, Verran (1987) subjective sleep questionnaire (SSQ) each used in a single study.…”
Section: Populationmentioning
confidence: 99%
“…A study on resistance and aerobic exercise training in women with generalized anxiety disorder (often comorbid with primary mood disorders) found that participants reported improved sleep initiation and continuation after six weeks. Furthermore, there was a significant relationship between generalized anxiety disorder clinical severity rating scores and sleep efficiency [62]. Given these preliminary findings on the benefits of exercise for sleep in anxiety disorders and insomnia, exercise may also be beneficial for sleep disturbance in mood disorders given the high rates of comorbid anxiety [4, 63–66].…”
Section: Exercise and Comorbid Conditions With Mood Disordersmentioning
confidence: 99%
“…Schuch et al, 2016;Chen et al, 2016), anxiety (see, e.g. De Souza Moura et al, 2015Herring et al, 2015), and in bipolar disorder (see, e.g., review by Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%